Overcoming water scarcity and quality constraints: Water and the Environment - Bos, Elroy; Bergkamp, Ger (International Food Policy Research Institute, 2001)
Water and ecosystems are inextricably linked. The ecosystems of our planet, and the plants and animals that live within them, need water for their survival.